2008
DOI: 10.1128/aac.00366-08
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmid-Borne bla OXA-58 Gene Confers Imipenem Resistance to Acinetobacter baumannii Isolates from a Lebanese Hospital

Abstract: Conjugation experiments demonstrated that resistance to imipenem could be transferred along with a plasmid containing the carbapenem-hydrolyzing oxacillinase bla OXA-58 gene. The plasmid that we called pABIR was 29,823 bp in size and showed a novel mosaic structure composed of two origins of replication, four insertion sequence (IS) elements, and 28 open reading frames. The bla OXA-58 gene was flanked by IS18 and ISAba3 elements at the 5 and 3 ends, respectively. The production of the carbapenem-hydrolyzing ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 28 publications
4
71
1
Order By: Relevance
“…In particular, the emergence of carbapenem resistance has been reported during hospital outbreaks of multidrug-resistant A. baumannii in Italy and southern Europe (4,8,11,13,20,21,(25)(26)(27)(28). Accordingly, the two A. baumannii clones described in the present study showed similar antibiotypes, characterized by resistance to all classes of antimicrobials, including carbapenems, and intermediate resistance to rifampin but susceptibility to colistin.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In particular, the emergence of carbapenem resistance has been reported during hospital outbreaks of multidrug-resistant A. baumannii in Italy and southern Europe (4,8,11,13,20,21,(25)(26)(27)(28). Accordingly, the two A. baumannii clones described in the present study showed similar antibiotypes, characterized by resistance to all classes of antimicrobials, including carbapenems, and intermediate resistance to rifampin but susceptibility to colistin.…”
Section: Discussionsupporting
confidence: 51%
“…PCR analysis for carbapenemase-encoding genes in Acinetobacter spp. (bla IMP , bla VIM , bla SIM , bla OXA-23 -like, bla OXA-24 -like, bla OXA-51 -like, and bla OXA-58 ) was performed as previously described (28). PCR characterization of the bla OXA-58 -surrounding insertion sequence (IS) was performed as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of the sequence of the bla OXA-58 gene from representatives of the A1, A2, and A3 clonal groups is in accordance with horizontal transfer of the gene between strains sharing the same hospital environment. The horizontal transfer of the bla OXA-58-like gene has been already demonstrated (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, however, the concomitant overproduction of different carbapenem-hydrolyzing enzymes was considered the main factor responsible for carbapenem resistance (21,26). In fact, the overproduction of OXA-type enzymes with the ability to hydrolyze carbapenems is generally considered the principal mechanism of A. baumannii carbapenem resistance (13,35,38,52). The overall observations suggested that CarO could differently contribute to reduced carbapenem susceptibility in different A. baumannii strains and/or play another role(s) in the pathophysiology of this opportunistic pathogen.…”
mentioning
confidence: 99%